(untitled) (Experimental biology, 2019)
The degree of pollution of the reservoirs of Northern Kazakhstan from year to year is growing steadily, due to the growth of the technogenic load on water sources. In this regard, studies to solve the problems of clearing open reservoirs from various pollutants are among the important measures to improve the ecological situation in the region. As a result of algalization of contaminated natural waters with strains of green microalgae Chlorella vulgaris И 2 and Parachlorella kessleri У 1, water quality indicators have been improving for 14 days: the amount of dissolved oxygen increases, the BOD5 values ​​in all samples decrease, the concentrations of sulfates, nitrites, nitrates, salts decrease ammonium, magnesium, chloride, copper, iron, zinc and manganese. The overall purification efficiency in both strains for nitrite was up to 62,5%, for ammonium salt - up to 65,7%, for copper - up to 60,7%, for iron – 51,9%, for zinc - up to 40%, for nitrates - up to 40,5%, manganese - up to 36,4%, sulfates – 25,6%, magnesium - up to 18,8% and chlorides - up to 5,6%. Due to the accumulating capacity of the strains Chlorella vulgaris И 2 and Parachlorella kessleri У 1 it is possible to carry out the process of effective bio-purification of contaminated natural as well as wastewater from pollutants of various origin. Key words: рollutants, microalgae, accumulating properties, heavy metals, water reservoir, algalization.